Developments in X-ray tomography characterization for electrochemical devices. (December 2019) - Heenan, Thomas M.M.; Tan, Chun; Hack, Jennifer; Brett, Dan J.L.; Shearing, Paul R.
Graphical abstract: Abstract: Over the last century, X-ray imaging instruments and their accompanying tomographic reconstruction algorithms have developed considerably. With improved tomogram quality and resolution, voxel sizes down to tens of nanometers can now be achieved. Moreover, recent advancements in readily accessible lab-based X-ray computed tomography (X-ray CT) instruments have produced spatial resolutions comparable to specialist synchrotron facilities. Electrochemical energy conversion devices, such as fuel cells and batteries, have inherently complex electrode microstructures to achieve competitive power delivery for consideration as replacements for conventional sources. With resolution capabilities spanning tens of microns to tens of nanometers, X-ray CT has become widely employed in the three-dimensional (3D) characterization of electrochemical materials. The ability to perform multiscale imaging has enabled characterization from system-down to particle-level, with the ability to resolve critical features within device microstructures. X-ray characterization presents a favorable alternative to other 3D methods, such as focused ion beam scanning electron microscopy, due to its non-destructive nature, which allows four-dimensional (4D) studies, three spatial dimensions plus time, linking structural dynamics to device performance and lifetime. X-ray CT has accelerated research from fundamental understanding of the links between cell structure and performance, to the improvement in manufacturing and scale-up of full electrochemical cells. Furthermore, this has aided in the mitigation of degradation and cell-level failures, such as thermal runaway. This review presents recent developments in the use of X-ray CT as a characterization method and its role in the advancement of electrochemical materials engineering.